Charles Sanders Peirce in his own words : 100 years of semiotics, communication and cognition - Thellefsen, Torkild; Sørensen, Bent; De Waal, Cornelis (Semiotics, communication and cognition, 2014)
"This book is published 100 years after the death of the American polymath Charles Sanders Peirce to celebrate the first century of scholarship on his work."--
Keywords: Peirce, Charles S : (Charles Sanders), : 1839-1914; Semiotics; Charles Sanders Peirce